Long-Term Risk of Ovarian Cancer and Borderline Tumors After Assisted Reproductive Technology. Issue 7 (July 2021) - Spaan, Mandy; van den Belt-Dusebout, Alexandra W.; Lambalk, Cornelis B.; van Boven, Hester H.; Schats, Roel; Kortman, Marian; Broekmans, Frank J. M.; Laven, Joop S. E.; van Santbrink, Evert J. P.; Braat, Didi D. M.; van der Westerlaken, Lucette A. J.; Cohlen, Ben J.; et al.
Abstract : (Abstracted from J Natl Cancer Inst 2021;113:699–709) Despite inconclusive evidence, concerns that assisted reproductive technology may be associated with increased risk of ovarian cancer remain. Significant increases in gonadotropin levels and disruption of ovarian epithelium have been proposed as mechanisms to explain this potential association.